Shrimp farming in Southwestern Bangladesh: a case study of economic impacts during COVID-19 (Asian Journal of Medical and Biological Research, 2021)
Bangladesh is endowed with a long coastline and therefore offers the enormous potential of marine wealth. In the coastal part of Bangladesh, shrimp is one of the most important export-oriented aquacultures due to high-profit return on the same value. Shrimp farming contributes significantly to the livelihoods of rural Bangladeshis in the southwestern region. It is critical to be aware of current culture practices and the measures shrimp farmers take to sustain the trend of exporting shrimp around the world. A random sampling was done of shrimp farmers in the Batiaghata Upazila of Khulna district to learn about the current state of shrimp farming and the challenges they are faced during COVID-19. The recent study reveals that most farmers following semi-intensive monoculture practice, application of organic sources in the shrimp pond, selection of PCR tested hatchery-produced Post Larvae (PL) and maintaining good hygiene practice that delivered considerable production of shrimp in this area. But in addition, with these good production farmers also face some difficulties. Some major shrimp diseases were identified in this study including White Feces Disease (WFD), White Spot Syndrome Virus (WSSV), Eosinophilia-Myalgia Syndrome (EMS), Black Gill Disease and some parasite attacks like Zutharium. Lower market price, flood and mortality are other constraints for shrimp farming. The low market price is the major issue for shrimp farmers nowadays around this pandemic situation. As a result, the government, donor agencies, planners, academics, and non-governmental organizations (NGOs) should come forward during the pandemic periods to assist farmers in resolving challenges and ensuring shrimp export revenues of Bangladesh are sustainable.Asian J. Med. Biol. Res. 2021, 7 (3), 273-283